Light- and temperature-dependent dynamics of chromophore and protein structural changes in bathy phytochrome Agp2. Issue 33 (17th August 2021) - Merga, Galaan; Lopez, Maria Fernandez; Fischer, Paul; Piwowarski, Patrick; Nogacz, Żaneta; Kraskov, Anastasia; Buhrke, David; Escobar, Francisco Velazquez; Michael, Norbert; Siebert, Friedrich; Scheerer, Patrick; Bartl, Franz; et al.
Abstract : Time-resolved vibrational spectroscopies reveal that phototransformation of the Pfr dark state of bacterial phytochrome Agp2 follows a branched mechanism with a productive and non-productive pathway. Abstract : Bacterial phytochromes are sensoric photoreceptors that transform light absorbed by the photosensor core module (PCM) to protein structural changes that eventually lead to the activation of the enzymatic output module. The underlying photoinduced reaction cascade in the PCM starts with the isomerization of the tetrapyrrole chromophore, followed by conformational relaxations, proton transfer steps, and a secondary structure transition of a peptide segment (tongue) that is essential for communicating the signal to the output module. In this work, we employed various static and time-resolved IR and resonance Raman spectroscopic techniques to study the structural and reaction dynamics of the Meta-F intermediate of both the PCM and the full-length (PCM and output module) variant of the bathy phytochrome Agp2 from Agrobacterium fabrum . In both cases, this intermediate represents a branching point of the phototransformation, since it opens an unproductive reaction channel back to the initial state and a productive pathway to the final active state, including the functional protein structural changes. It is shown that the functional quantum yield, i.e. the events of tongue refolding per absorbed photons, is lower by a factor of ca. two than the quantum yield of the primary photochemical process. However, the kinetic data derived from the spectroscopic experiments imply an increased formation of the final active state upon increasing photon flux or elevated temperature under photostationary conditions. Accordingly, the branching mechanism does not only account for the phytochrome's function as a light intensity sensor but may also modulate its temperature sensitivity.